Kajian Kritik Naratif Terhadap Pemaknaan Kasih Allah di Tengah Konsekuensi Keberdosaan Manusia Dalam Kejadian 3:1-24 dan Implementasinya Bagi Kehidupan Milenial - Gagola, Megaputri Prasetyawati (Peneliti.net, 2024)
God's love for humans from the beginning He created until humans fell into sin has never changed. Humans are the only creation created in the image and likeness of God, humans are given the place to preserve and rule over everything that has been created by God. But human actions full of pride ultimately lead them to fall into sin. Every action has consequences and they must be able to take responsibility. God indeed punished them for violating commands that He had forbidden. But in the text of Genesis 3:1-24, God's love for humans is clearly illustrated. The purpose of this research is so that we will be more aware that God's love is true love that He gave not only to Adam and Eve but to this day. Even though sometimes consciously or unconsciously we commit many sins against Him. But no matter how big the sin we commit, it is certainly greater than God's love for all of His creation.